Suppression of Vibration Using Passive Receptance Method with Constrained Minimization - Murat Tursun; Eşref Eşkinat (Shock and Vibration)
Structural vibration analysis is used to suppress unwanted vibrations in many areas such as aerospace engineering, manufacturing, defense, automotive, etc. As a result of suppressing the unwanted vibration, the quality of the product is improved. Focusing on the minimization of the vibration amplitudes via a concept of receptance, a new and efficient method for calculating the receptance of a translational mass-spring-damper system with N masses and M absorbers (where N and M are any positive integer) is developed. The receptance of the combined system, in terms of the parameters of the main and absorber systems is derived, separately. The optimal parameters of the absorbers are then found. A methodology is derived using dynamic stiffness and linear graph representation in order to verify the dynamic stiffness, i.e., the inverse of the receptance, of the system.